2000
DOI: 10.1002/pc.10178
|View full text |Cite
|
Sign up to set email alerts
|

Modulus recovery kinetics and other insights into the payne effect for filled elastomers

Abstract: The nonlinear viscoelastic behavior of filled elastomers is examined in detail using a variety of samples including carbon-black filled natural rubbers and fumed silica filled silicone elastomers. New insights into the Payne effect are provided by examining the generic results of sinusoidal dynamic and constant strain rate tests conducted in true simple shear both with and without static strain offsets. The effect of deformation history is explored by probing the low amplitude modulus recovery kinetics resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
135
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 16 publications
9
135
2
1
Order By: Relevance
“…Additionally, a static strain has no effect on the observed Payne effect. 3 Why would a glassy layer disappear when subjected to a static stress but not a dynamic stress? In summary, the glassy layer as a root cause of the reinforcement mechanism raises more questions than it answers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, a static strain has no effect on the observed Payne effect. 3 Why would a glassy layer disappear when subjected to a static stress but not a dynamic stress? In summary, the glassy layer as a root cause of the reinforcement mechanism raises more questions than it answers.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that the Payne effect is related to the dynamic, and not static, component of the strain history and that the Payne effect would vanish at very low strain rates. 3 If a glassy layer is responsible for the high reinforcement then why does reinforcement vanish if observed at a slow strain rate? Additionally, a static strain has no effect on the observed Payne effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Viscoelastic behavior is extremely sensitive to the structure of the filler network in particlereinforced polymers, and the strain-dependence of dynamic mechanical response after complex deformation histories can reveal details of the heterogeneity and kinetics of network break-up and recovery. [48][49][50][56][57][58][59][60] When the particles are electrically conductive (e.g., carbon black), electrical resistance testing is another useful method to study the structure of the percolated filler network. [61][62][63][64] With the exception of transmission electron microtomography, 65,66 it is difficult to observe differences in the three-dimensional nature of jammed particle networks using microscopy.…”
Section: Flocculation Reinforcement and Glass Transition Effects 511mentioning
confidence: 99%